2005
DOI: 10.1080/0142639042000324794
|View full text |Cite
|
Sign up to set email alerts
|

“It Gets You Away From Everyday Life”: Local Woodlands and Community Use—What Makes a Difference?

Abstract: This paper explores who uses woodlands near their homes, why they visit, what benefits they believe they obtain and what makes the difference between them choosing to visit or not. In the research, supported by the Forestry Commission, a multi-method, user-led approach was used, based on focus groups, questionnaire surveys and on-site observation in relation to five different communities in the central belt of Scotland. The conclusions demonstrate the overriding importance of childhood woodland visits as predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 25 publications
1
49
0
3
Order By: Relevance
“…Retrospective studies have shown the importance of childhood nature experiences to adult environmental attitudes and preferences (Ward Thompson, Aspinall, Bell & Findlay, 2005;Wells & Lekies, 2006). Thus, we considered it important to include the importance of childhood experiences of nature to our potential determinants of restorative experiences.…”
mentioning
confidence: 99%
“…Retrospective studies have shown the importance of childhood nature experiences to adult environmental attitudes and preferences (Ward Thompson, Aspinall, Bell & Findlay, 2005;Wells & Lekies, 2006). Thus, we considered it important to include the importance of childhood experiences of nature to our potential determinants of restorative experiences.…”
mentioning
confidence: 99%
“…The attractiveness of a forest is that it provides a much more pleasant ambience for physical activity and, if it is large enough, it can accommodate a range of different forms of recreation which promote physical health, mental restoration and aesthetic pleasure all at once. Research on local woodland use by communities in Scotland showed that the predominant use is for walking and cycling, suggesting that forests can play a key role in maintaining healthy and active lifestyles for all ages and both sexes (Ward Thompson et al, 2004Thompson et al, : 2005. Compared with streets or small open spaces, forests provide a much more pleasant environment with less pollution, cleaner air to breathe while exercising and potentially the beneficial effects of aromatic hydrocarbons.…”
Section: Forests Physical Activity and Healthmentioning
confidence: 99%
“…The most frequent recreational activities were dog walking (8.9%), walking for leisure (8.3%) and standing or sitting to discuss with acquaintances or friends (4.9%). So, walking seems to be a main group of recreational activities in a naturalistic green space network as it is in other types of urban green space (Ward-Thompson, 2005;Bell et al, 2004;Moore, 2003;Dunnett et al, 2002).…”
Section: Observational Studymentioning
confidence: 99%
“…A common finding amongst surveys of the recreational use of urban green spaces is that sports users are the minority of all users of parks and that informal activity is more common than formal activity (GreenSpace, 2007;Mulder et al, 2005;Ward-Thompson, 2005;Bell et al, 2004;Moore, 2003;Dunnett et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation